Intracellular localization of Crimean-Congo Hemorrhagic Fever (CCHF) virus glycoproteins - Fernando Lisa; Haferkamp Sebastian; Schwarz Tino F; Feldmann Heinz; Flick Ramon (Virology Journal, 2005)
Abstract Background Crimean-Congo Hemorrhagic Fever virus (CCHFV), a member of the genus Nairovirus, family Bunyaviridae, is a tick-borne pathogen causing severe disease in humans. To better understand the CCHFV life cycle and explore potential intervention strategies, we studied the biosynthesis and intracellular targeting of the glycoproteins, which are encoded by the M genome segment. Results Following determination of the complete genome sequence of the CCHFV reference strain IbAr10200, we generated expression plasmids for the individual expression of the glycoproteins GN and GC, using CMV- and chicken β-actin-driven promoters. The cellular localization of recombinantly expressed CCHFV glycoproteins was compared to authentic glycoproteins expressed during virus infection using indirect immunofluorescence assays, subcellular fractionation/western blot assays and confocal microscopy. To further elucidate potential intracellular targeting/retention signals of the two glycoproteins, GFP-fusion proteins containing different parts of the CCHFV glycoprotein were analyzed for their intracellular targeting. The N-terminal glycoprotein GN localized to the Golgi complex, a process mediated by retention/targeting signal(s) in the cytoplasmic domain and ectodomain of this protein. In contrast, the C-terminal glycoprotein GC remained in the endoplasmic reticulum but could be rescued into the Golgi complex by co-expression of GN. Conclusion The data are consistent with the intracellular targeting of most bunyavirus glycoproteins and support the general model for assembly and budding of bunyavirus particles in the Golgi compartment.